Comparative Analysis of Financial Performance of Conventional Bank With BUMD Sharia Bank Riau Kepri - Listiana, Mia; Halim, Edyanus Herman; Efni, Yulia (Basecamp Economics PubMed, 2024)
This study was conducted This research was conducted on conventional and sharia Riau Riau Riau banking in Riau. The purpose of this research is to compare the financial performance between Bank Riau Kepri Syariah and Bank Riau Kepri Conventional in Indonesia using financial ratios for the period 2021 to 2023. The financial ratios used to measure bank financial performance consist of the CAR, NPL, BOPO ratios. , LDR, ROA, and ROE. The population in this research is conventional Bank Riau Kepri and Bank Riau Kepri sharia. This research was carried out through different t-test analysis.The results of the research show that: (1) There is a significant difference in the CAR ratio when analyzed using the Paired Samples Test, (2) There is a significant difference in the NPL ratio of conventional banks and Islamic banks in Riau, Kepri, (3) There is a significant difference in BOPO ratio of conventional banks and Islamic banks in Riau, (4) There is a significant difference in the LDR ratio of conventional banks and Islamic banks in Riau, (5) There is a significant difference in the ROA ratio of conventional banks and Islamic banks in Riau, Kepri and (6) There is a difference significant to the ROE ratio of conventional banks and Islamic banks in Riau, Kepri. The overall results of the research are that there are significant differences in the financial performance of conventional banks and Syari'ah Banks in Roau Kepri.